Renal Physiology and Water Homeostasis Modules (Out of Print) - Joel Gordon (Association of American Medical Colleges, 2006)
Abstract This resource is a series of eight interactive, animated modules covering renal physiology and water homeostasis. At our institution, target learners were first-year medical students in our integrated human organ systems physiology-histology course. The water homeostasis module content is a detailed explanation of the control of water homeostasis, which features a detailed animation of how antidiuretic hormone works in the renal tubular system. Student feedback from the last 2 years regarding these modules indicates they are highly effective for delivering high-quality animations depicting activities in renal tissue that mimic real-time physiology. These modules have shown our faculty and our students that effective presentations are not the sole domain of Microsoft software and that other forms of software and electronic presentations can be just as effective.